Mix Method Impact of Exposure of Inhalants Exposure “Glueing” on Street Children Community in Kendari City - Asbath Said; Mikawati Rasyid; Wa Ode Nova Novianti R; Lodes Hadju (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: The results of the preliminary survey conducted by researchers before the research began and supported by statements provided by the informants, supported the researchers' allegations and found that there was a phenomenon of inhalent abuse in street children in Kendari City, namely using fox and disgrace type glue to create a comfortable effect (fly) against themselves. Objectives: This study aims to determine the impact of chronic exposure to gluing inhalants on the community of children in Kendari city. Methods: This study uses the Mix Method, which is a combination of a quantitative approach and a qualitative approach with snowball sampling technique, the number of respondents is 10 people. Results: The research results from the physiological aspects, namely; Respiratory rate of street children who “glueing” on average is high, there are 2 abnormal people, Heart Rate of street children who are “glueing” on average is weak, there are 9 people who are abnormal, Weight and height of street children who are “glueing” in the categories are insufficient while the body temperature and blood pressure of street children who are “glueing” are all still within normal limits. Conclusion: There is a psychological impact from inhaling glue which makes informants feel hallucinating and make them feel calm. It is recommended to the Kendari city government that street children need special attention, because they are a group that is very vulnerable to the negative impacts of the environment and they need special guidance regarding impacts the physiology and psychology of gluing.